FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN KEMAMPUAN MELAKUKAN DETEKSI HIPOGLIKEMIA PADA PASIEN DIABETES MELLITUS TIPE 2 - Cut Husna; Bahagia Akmal Saputra (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2020)
Hypoglycemia is a condition characterized by measured blood sugar levels that are lower than normal values in type 2 diabetes mellitus (DM) patients. The impact of hypoglycemia cause a decrease in peripheral tissue perfusion resulting in decreased consciousness. Hypoglycemia detection is useful to early detect of the symptoms of hypoglycemi, hence it could be treated quickly and accurately. The purpose of this study is to determine the related factors (age, knowledge, long-term of diabetes mellitus, and the availability of blood glucose measuring devices) with the ability to detect hypoglycemia in patients with diabetes mellitus tipe 2 at a provincial hospital of Banda Aceh. This study used a descriptive correlative design. The study population was all diabetes mellitus type 2 patients who experienced hypoglycemia who visited to the Endocrine Polyclinic at a provincial hospital in Banda Aceh in 2018 totaling 1,364. The sampling used in this study is a purposive sampling technique for 99 respondents. Data collection using a questionnaire in a Gutman scale totaling 25 statements. The questionnaire reliability tested used Cronbach alpha = 0.955. Data were analyzed using the Chi-square test (α = 0.05). The results showed that no relationship between patient’s age with hypoglycemia detection ability (p=0.322), there was a relationship between knowledge with hypoglycemia detection ability (p=0.003), there was no relationship between long-term of diabetes mellitus with hipoglycemia detection ability (p=0.157), and there was a relationship between the availability of an independent glucose check (glucometer) with hypoglycemia detection ability (p=0.049). Based on the results, patient knowledge, availability of glukometer have a significantly affects on the ability to detect hypoglycemia. It is recommended to nurses in hospitals to increase knowledge of early detection of hypoglycemia in patients, education in using glucose check, and routine blood sugar checks in patients with diabetes mellitus.